Assessment of the impact of labor productivity on the effectiveness of innovative activities in Kazakhstan and the Northwestern Federal District of Russia - Roslyakova, N.; Vechkinzova, E. (BUKETOV BUSINESS REVIEW, 2021)
Object: In many foreign countries, growth in labor productivity leads to a reduction in working hours. But these processes are not always proportional and depend on the correlation of social and economic priorities of states, on the conditions of general globalization and neoliberalization. The unfavorable ratio of the internal price proportions of some states and the low level of development of technics and technology act as obstacles to increasing the rate of economic growth. In such conditions, a reduction in working hours will inevitably lead to a reduction in the country's economic potential and the level of income of citizens. The purpose of this article is to study the nature of labor productivity and analyze the relationship between the proportions of labor productivity and the volume of production of innovative products in Russia and Kazakhstan as the largest EAEU states that determine development trends in the region. Methods: The collected data on the relationship between labor productivity and the volume of output of innovative products were analyzed using cluster analysis and nonparametric Data Envelopment Analysis (DEA). Findings: Labor productivity affects the level of innovative development and affects the overall economic development of individual regions and countries as a whole. The analysis of these processes is very important for the formation of state development policy. Therefore, this study examines the relationship between labor productivity and the volume of innovative products, as well as examines similar processes in certain regions of Russia and Kazakhstan. Conclusions: According to the results obtained, the following hypotheses were accepted: in Kazakhstan and Russia, labor productivity directly affects the innovative production of products. This influence is different in the regions of both countries. In Kazakhstan and Russia, there are regions that are similar in characteristics of the processes of the impact of labor productivity on innovative output, and for them similar measures to improve state policy are recommended